Calculation of Theoretical and Empirical Nutrient N Critical Loads in the Mixed Conifer Ecosystems of Southern California. (2007) - Breiner, Joan; Gimeno, Benjamin S.; Fenn, Mark
Abstract : Edaphic, foliar, and hydrologic forest nutrient status indicators from 15 mixed conifer forest stands in the Sierra Nevada, San Gabriel Mountains, and San Bernardino National Forest were used to estimate empirical or theoretical critical loads (CL) for nitrogen (N) as a nutrient. Soil acidification response to N deposition was also evaluated. Robust empirical relationships were found relating N deposition to plant N uptake (N in foliage), N fertility (litter C/N ratio), and soil acidification. However, no consistent empirical CL were obtained when the thresholds for parameters indicative of N excess from other types of ecosystems were used. Similarly, the highest theoretical CL for nutrient N calculated using the simple mass balance steady state model (estimates ranging from 1.4–8.8 kg N/ha/year) was approximately two times lower than the empirical observations. Further research is needed to derive the thresholds for indicators associated with the impairment of these mixed conifer forests exposed to chronic N deposition within a Mediterranean climate. Further development or parameterization of models for the calculation of theoretical critical loads suitable for these ecosystems will also be an important aspect of future critical loads research.